Divine fertility : the continuity in transformation of an ideology of sacred kinship in Northeast Africa - Mire, Sada, 1977- (Abingdon, Oxon; New York, NY : Routledge, 2020)
"This book uniquely explores the impact of indigenous ideology and thought on everyday life in Northeast Africa. It examines the potential continuity of the rituals, symbolism and practices of indigenous religious institutions in the currently Christian and Muslim Horn of Africa. It thus bridges both the disciplines of anthropology and archaeology and past and present times. Furthermore, in highlighting the diversity in pre-Christian, pre-Islamic regional beliefs and practices that extend beyond the dominant narratives and simplistic political arguments of current religions, the study shows that for millennia complex indigenous institutions have bound people together beyond the labels of Christianity and Islam; they have sustained peace through ideological exchange and tolerance (if not always complete acceptance). Through recent archaeological and ethnographic research, the concepts, landscapes, materials and rituals believed to be associated with the indigenous and shared culture of the Sky-God belief are examined. The author makes sense, for the first time, of the relationship between the notion of sacred fertility and a number of regional archaeological features and on-going ancient practices including FGM and other physically invasive practices, rain-making and the ritual hunt. This archaeological study of the pre-Christian and pre-Islamic heritage of the Horn of Africa and Northeast Africa is the first to put forward a theoretical and analytical framework for the interpretation of the shared regional heritage and the indigenous archaeology of the region. It will be invaluable to archaeologists, archaeologists and historians interested in Northern Africa"--
Introduction: Aims, structure, concepts, terminology, the movement of peoples and ideas -- Sacred landscapes, materiality and fertility rituals -- Material culture, fertility and sacrifice at the sacred site of Aw-Barkhadle -- In the name of divine kinship: the fertility bath, Bun Shuruur, Baanshada Dumarka, Zar, Sitaat, Wagar, Gudnid Fircooni (FGM) Waqlaal and Istunka -- Sacred fertility of a divine kinship ideology: indigenous institutions and Sufi Islam in the Horn of Africa -- An ideology of fertility in the archaeology of the Horn of Africa: Aw-Barkhadle and beyond -- Conclusions: Divine fertility of a sacred kinship ideology.
OCLC-licensed vendor bibliographic record.
Keywords: Fertility cults -- Africa, Northeast; Kinship -- Africa, Northeast -- Religious aspects; Indigenous peoples -- Africa, Northeast -- Religion; Africa, Northeast -- Social life and customs; SOCIAL SCIENCE / Archaeology